SET-JETTING IN THE REPUBLIC OF MACEDONIA - Mijalov, Risto; Kitevski, Goran; Iliev, Dejan (MACEDONIAN GEOGRAPHICAL SOCIETY, 2015)
The paper will highlight the newer alternative form of tourism with it’s possible aspects of enforcement in our country. Besides the basic function of the set-jetting, in the paper will be placed an attempt to deepen the theory of the set-jetting and its function, by setting the factors and potential for creating such alternative value of tourism.